Increased incidence of faecal Klebsiella pneumoniae in patients with HLA B7 CREG antigen and men with rheumatoid arthritis. Issue 6240 (30th August 1980) - Ebringer, R; Colthorpe, D; Young, A; Corbett, M
Abstract : In a study of the carriage of faecal Klebsiella pneumoniae in 106 patients with rheumatoid arthritis the incidence of carriage was higher in men (28%) than women (14%) (p < 0.001) and klebsiellae were isolated on two or more occasions from a higher proportion of men than women (p < 0.002). The incidence of carriage was increased among patients with rheumatoid arthritis who had B7 cross-reacting (B7 CREG) antigens (32% v 13%--p < 0.001). Carriage of klebsiellae was not associated with clinical disease activity, raised erythrocyte sedimentation rate, drug treatment, or the presence of HLA Dw4 or DRw4 or both. Thus the carriage and prevalence of faecal Klebsiella pneumoniae appear to be partly determined by the sex and HLA state of the host.